THE READINESS OF UPSI TEACHER TRAINEES FOR ARABIC LANGUAGE IN THE IMPLEMENTATION OF CLASSROOM-BASED ASSESSMENT DURING TEACHING PRACTICE - Zakaria, Zarima Mohd; Mei, Fatimah Suo Yan; Lambri, Alizah; Yusuf, Robe’ah; Sukadari, (International Journal of Psychosocial Rehabilitation, 2020)
Classroom-based assessment (CBA) is an assessment which evaluates the aspects of cognitive (intellectual), affective (emotional and spiritual) and psychomotor (physical) holistically based on the Standard-Based Curriculum for Secondary Schools and the National Education Philosophy (NEP). This study aims to investigate the level of readiness among Arabic teacher trainees in Universiti Pendidikan Sultan Idris (ATTsUPSI) focusing on the knowledge of classroom-based assessment, the levels of assessment in the four language skills and the challenges faced throughout the assessment process during their teaching practice (TP). 73 teacher trainees of the Arabic with Education (AT49) program, UPSI, who went through the teaching practice in semester A171 Session 2017 were selected as the respondents for this study. Questionnaire was used as the research instrument in this study which was analysed using Statistical Packages for Sosial Science (SPSS) version 23 presented through descriptive statistics and inferential statistics. The research findings indicate that the level of CBA literacy knowledge of ATTs UPSI is at the low level (mean=1.82, sd= .53). Whereas the practices of CBA among ATTs UPSI for all the four language skills, listening and speaking, reading and writing, is at the high level: the practices of assessment for the listening and speaking skills has recorded the highest mean (mean=3.86, sd=.84), followed by the writing skills (mean=3.65, sd=.89) and the reading skills (mean=3.53, sd=.83). In the aspect of the challenges, the findings indicate that the mean is at the average level (mean=2.40, sd=.58). The implication of this study has highlighted that the ATTs need to improve their knowledge in CBA in KPD3016 and KPD3026 courses to ensure it is in line with the practices of CBA during their teaching practice.